4DMRI-based investigation on the interplay effect for pencil beam scanning proton therapy of pancreatic cancer patients - Dolde, Kai; Kachelrieß, Marc; Naumann, Patrick; Saito, Nami; Pfaffenberger, Asja (Radiation oncology, 2019)
Background: Time-resolved volumetric magnetic resonance imaging (4DMRI) offers the potential to analyze 3D motion with high soft-tissue contrast without additional imaging dose. We use 4DMRI to investigate the interplay effect for pencil beam scanning (PBS) proton therapy of pancreatic cancer and to quantify the dependency of residual interplay effects on the number of treatment fractions. Methods: Based on repeated 4DMRI datasets for nine pancreatic cancer patients, synthetic 4DCTs were generated by warping static 3DCTs with 4DMRI deformation vector fields. 4D dose calculations for scanned proton therapy were performed to quantify the interplay effect by CTV coverage (v95) and dose homogeneity (d5/d95) for incrementally up to 28 fractions. The interplay effect was further correlated to CTV motion characteristics. For quality assurance, volume and mass conservation were evaluated by Jacobian determinants and volume-density comparisons. Results: For the underlying patient cohort with CTV motion amplitudes < 15 mm, we observed significant correlations between CTV motion amplitudes and both the length of breathing cycles and the interplay effect. For individual fractions, tumor underdosage down to v95 = 70% was observed with pronounced dose heterogeneity (d5/d95 = 1.3). For full × 28 fractionated treatments, we observed a mitigation of the interplay effect with increasing fraction numbers. On average, after seven fractions, a CTV coverage with 95–107% of the prescribed dose was reached with sufficient dose homogeneity. For organs at risk, no significant differences were found between the static and accumulated dose plans for 28 fractions. Conclusion: Intrafractional organ motion exhibits a large interplay effect for PBS proton therapy of pancreatic cancer. The interplay effect correlates with CTV motion, but can be mitigated efficiently by fractionation, mainly due to different breathing starting phases in fractionated treatments. For hypofractionated treatments, a further restriction of motion may be required. Repeated 4DMRI measurements are a viable tool for pre- and post-treatment evaluations of the interplay effect.
Gesehen am 15.08.2019